Relationship Between Family Support and Cadres with Mother Activity Weighing Toddlers - Lassa, Febi; Sinaga, Masrida; Takaeb, Afrona E.L (Faculty of Public Health, Nusa Cendana University, 2021)
relationship between family support and cadres with the activity of mothers weighing toddlers at the Posyandu, Toobaun Village,West Amarasi District. The type of research used is an analytic survey with a cross sectional research design. The population and sample in this study were mothers who had toddlers (12-59 months) whose names were registered at the posyandu Toobaun Village and had KMS. The sample is 65 people. The sampling technique used is simple random sampling. The data collection technique in this study was to look at the register book and interview using a prepared questionnaire. The instruments used in this study were questionnaires and posyandu register books (cadres weighing records). The data analysis technique used Chi-square test with 95% confidence level (α= 0.05). The results showed that family support (p-value = 0.000) and cadre support (p-value = 0.000) were related to the activities of mothers weighing toddlers at the posyandu, Toobaun Village, Amarasi Barat District. It is hoped that the puskesmas and the Toobaun Village Government can work together to create training activities to improve skills for health workers and cadres as well as make health promotion activities in the community about the importance of bringing toddlers to the posyandu